2022
DOI: 10.1177/20413866221082128
|View full text |Cite
|
Sign up to set email alerts
|

Rivalry and performance: A systematic review and meta-analysis

Abstract: Rivalry, a relational competition, is known to increase motivation and performance. However, a systematic review and meta-analysis that examines the effect sizes is lacking. Further, most research on this topic has not considered the type of rivalry (individual versus collective) and the research field as potential moderators. We conducted a wide-scale search, looking for rivalry and performance studies, which yielded 22 papers (k = 35) with 27,771 observations that were systematically reviewed. Eighteen paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…The notion that employees show positive behaviors in response to more distal status threats also aligns with a growing body of research on the positive consequences of status threat and rivalry (Lee & Duffy, 2019;Milstein et al, 2022;Schaubroeck & Lam, 2004). In contrast to the more traditional view on status threat as a purely destructive phenomenon (Dunn & Schweitzer, 2006), this line of research highlights that employees may increase their job performance (Schaubroeck & Lam, 2004) or learn from a more successful coworker (Lee & Duffy, 2019).…”
Section: Discussionmentioning
confidence: 67%
“…The notion that employees show positive behaviors in response to more distal status threats also aligns with a growing body of research on the positive consequences of status threat and rivalry (Lee & Duffy, 2019;Milstein et al, 2022;Schaubroeck & Lam, 2004). In contrast to the more traditional view on status threat as a purely destructive phenomenon (Dunn & Schweitzer, 2006), this line of research highlights that employees may increase their job performance (Schaubroeck & Lam, 2004) or learn from a more successful coworker (Lee & Duffy, 2019).…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, a significant association between years of sports training and moral competence levels was proved in college-age students in an earlier study by Bronikowska et al [4]. However, this relationship only applied to male respondents (aged [19][20][21][22][23][24] professionally engaged in sports for a long time whose levels of moral competency was assessed as high. The opposite outcome was found with female peer respondents where higher levels of moral competency was presented by sportswomen with a shorter involvement in professional sports.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis review Milstein et al [19] found that the relationship between rivalry and performance is more robust for individual rivalry compared to group rivalry. The findings have been analyzed further and indicated that for a group rivalry correlations were positive with significant impact only in sports and, when analyzed in outside-of-sport world only in donation-raising organizations.…”
Section: Introductionmentioning
confidence: 99%